Diversity and succession of the microbial community and its correlation with lipid oxidation in dry-cured black carp (Mylopharyngodon piceus) during storage. (September 2021) - Zhang, Qi; Chen, Xiaocao; Ding, Yuting; Ke, Zhigang; Zhou, Xuxia; Zhang, Jianyou
Abstract: This study aimed to achieve deeper insights into the microbiota composition and dynamic succession of the dry-cured black carp during storage using a high-throughput sequencing technique (HTS). The effect of lipid oxidation on microorganisms was also evaluated. Over 651 bacterial genera belonging to 37 phyla were identified. Firmicutes, Proteobacteria and Actinobacteria were the main bacterial phylum, some are highly associated with meat spoilage. Staphylococcus, Macrococcus and Acinetobacter were the most three microbial genera throughout the entire storage period (30 days). Between two different storage temperature, refrigeration at 4 °C could facilitate maintaining the microbial diversity, while 25 °C storage led to the formation of dominant microflora and the reduction of community diversity. Canonical correspondence analysis (CCA) showed that acid value (AV), malondialdehyde (MDA) and 4-hydroxy-2-hexenal (HHE) contents were three key environmental factors (oxidation products) affecting the profile of the microbiota. Staphylococcus presented a positive correlation with HHE content, while Macrococcus and Acinetobacter were negatively correlated with HHE content. These results could expand our knowledge on the effect of lipid oxidation on change of microbial distribution, it could also present an guideline to develop advanced storage methods for the vacuum packed dry-cured fish products. Highlights: Microbial community structure was affected by the storage temperature. 4 °C refrigeration facilitated maintaining the diversity of the microbiota. Storage at 25 °C was prone to the formation of dominant microflora. Firmicutes, Proteobacteria and Actinobacteria were dominant species in samples. MDA, HHE and AV were the main factors affecting the distribution of bacteria.